POSTGRADUATE EDUCATION OF DOCTORS: CURRENT STATE AND PERSPECTIVES - Tsekhmister, Yaroslav; Lysenko, Oleksandra (The Modern Higher Education Review, 2017)
The article characterizes the system of postgraduate training of doctors in Ukraine, in particular it describes its organizational structure that is implemented through compulsory (internship and improvement) and variable (clinical residency, re-training, advanced training) components; defines the perspective for implementation of doctors’ residency in our state; determines the expediency in implementation of centralized life-long education provision system through establishment of self-governing organization, which activity will be directed to provide with efficient informal function of system of continuous professional education for doctors.